The Impact of the Zoning System on the Professional Development of English Teachers - Muslem Muslem; Nina Afrida; Apriliana Zura (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
Progress in a person's life can be seen based on the level of knowledge they have. Education is one way to help people reach their full potential both academically and non-academically so they can fulfill the essential functions and goals of national education. The study aimedto determine the impact of the zoning system on learning English and the challenges for English teachers when the zoning system was implemented at SMPN 1 Langsa. This study used a qualitative method using an ethnographic approach. This research was conducted at SMPN 1 Langsa with the subject of three English teachers. The data collection techniques used were observation and interviews. The results showed that: 1) The teaching and learning process is not conducive due to the lack of student discipline in learning. 2) The lack of politeness of students when talking to teachers in class. 3) The lack of student motivation to learn English. This research also showed that the challenges for English teachers during the implementation of this zoning system are that teachers must be more assertive in managing students, be extra in teaching students from the basics again in order to achieve learning objectives, and must conduct inclusive education training to deal with students with special needs.